(untitled) (Boletin Médico de Postgrado, 2022)
With the objective of determining the usefulness of the Modified Abdominal Trauma Index (ATIm) as a predictor of postoperative morbidity and mortality in patients with abdominal injuries who were attended at the Servicio de Cirugía of the Hospital Central Universitario Dr. Antonio María Pineda during the period December 2018-January 2019 a cross-sectional descriptive study was carried out with a sample of 28 patients, with an average age of 28.21 ± 12.78 years; the principal mechanism of trauma was by single-shot firearm (46.43%) and the most injured organs were colon (42.86%) and jejunum (32.14%). The most common surgical technique performed was repair or primary raffia (71.43%). Of the physiological and circumstantial factors described the time between trauma and surgical intervention was less than 6 hours (60.71%), 46.43% of cases did not present shock while 64.29% did not show contamination. Postoperative morbidity was 28.57%; postoperative mortality was 3.57%. Thus, for postoperative complications, the standard ATI was 25% and the modified ATI was 10% (p < 0.005). The modified ATI showed a sensitivity of 75% and specificity of 15% to predict complications in comparison with the standard ATI that reported a sensitivity of 87.5% and specificity of 15%. These results show the utility of physiological parameters added to the use of the anatomical variables of the ATI which allows a prediction of postoperative morbidity and mortality in patients with abdominal trauma.